Ketersediaan Nitrogen dan Pertumbuhan Selada (Lactuca sativa L.) pada Tanah Podsolik yang Diaplikasikan Azola (Azolla pinnata) - Hayatun Nupus; Syaifuddin Syaifuddin; Akhmad Rizalli Saidy (Acta Solum, 2024)
Podzolic soil is marginal land for agriculture because low N availability and low lettuce plant growth production can be overcome by appropriate fertilization. This study aimed to determine the effect of fresh Azola application on nitrogen availability, number of leaves, and fresh weight of lettuce plants on Podzolic soil. This research employed a single factor of completely randomized design (CRD), in which the treatments were: A0= control, A1= fresh Azola 4 t ha-1, A2= fresh Azola 8 t ha-1, A3= fresh Azola 12 t ha-1, A4= fresh Azola 16 t ha-1. Soil chemical characteristics: soil pH, contents of total N, NH4+, NO3-, organic C, and cation exchangeable capacity were determined on the 21st after incubation, while plant height and plant fresh weight were observed at harvest. The research results showed that increasing the amount of fresh Azola applied to the soil resulted in a tendency to increase soil pH, total N-content, N-NH4+, N-NO3-, number of plant leaves, and fresh weight of lettuce plants.